Integrasi Nilai-Nilai Kristiani Dan Ilmu Seksologi Tentang Hubungan Seksual Suami Istri Serta Perannya terhadap Keharmonisan Keluarga - JAKSON TOISUTA (Sekolah Tinggi Alkitab Penyebaran Injil Majalengka, 2025)
This study examines a holistic understanding of sexual relations within Christian marriage by integrating theological and scientific perspectives. According to the Bible, sexual intimacy between husband and wife is a sacred gift from God—not merely the fulfillment of biological needs, but a profound expression of communion within the marriage covenant. The relational, procreative, recreational, and symbolic functions of sex affirm its spiritual and ethical value. Meanwhile, the fields of sexology and health highlight the role of sexual intimacy in shaping identity, self-esteem, and the emotional and physical well-being of both partners. Healthy sexual satisfaction has been shown to contribute significantly to the quality of relationships and overall family welfare. The study concludes that a comprehensive and contextual understanding of sexuality in marriage can serve as a foundational factor for building harmonious families. In this regard, the Church holds a strategic role as an agent of education and formation, bridging knowledge gaps and fostering the moral awareness of its congregation. It is recommended that churches offer biblically grounded, open, and contextually relevant instruction on marital relationships as an integral part of transformative pastoral ministry.